Method for resource utilization of lithium-containing aluminum electrolyte

By calcining, leaching, heating reaction and calcining the lithium-containing aluminum electrolyte, the problems of low lithium yield and fluorine element corrosion are solved, and efficient recycling and utilization of resources are achieved.

CN119637914APending Publication Date: 2025-03-18XINXIANG TIANLI ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995591.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, when dealing with lithium-containing aluminum electrolytes, lithium yield is low, resources are not fully utilized, and fluorine elements cause corrosion to industrial equipment, increasing operating costs and safety hazards.

Method used

By first calcining the lithium-containing aluminum electrolyte powder and the fluorine-fixing agent, clinker is obtained, and water is added for the first leaching, and calcium fluoride and leaching liquid are separated. The soluble aluminum salt and soluble sodium salt were added to the leaching solution, and the heating reaction was carried out to obtain lithium aluminum co-precipitation. After the second calcination and the second leaching, a lithium-containing liquid and alumina were obtained, and lithium carbonate was obtained by removing impurities and reacting with carbonate.

Benefits of technology

It effectively reduces the corrosion of fluorine elements on the equipment, improves the yield of lithium, and realizes the comprehensive recycling of fluorine, aluminum and lithium, maximizing the utilization of lithium-containing aluminum electrolyte resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637914A_ABST
    Figure CN119637914A_ABST
Patent Text Reader

Abstract

The invention provides a method for recycling lithium-containing aluminum electrolyte, and relates to the field of recycling of lithium-containing aluminum electrolyte. The method for recycling the lithium-containing aluminum electrolyte comprises the following steps: carrying out first roasting on lithium-containing aluminum electrolyte powder and a fluorine fixing agent to obtain clinker; adding water into the clinker for first leaching, and separating to obtain calcium fluoride and leachate; adding soluble aluminum salt and soluble sodium salt into the leachate, and carrying out heating reaction under an alkaline condition to obtain lithium-aluminum coprecipitate; carrying out second roasting on the lithium-aluminum coprecipitate, adding water into the material subjected to second roasting, and carrying out second leaching to obtain lithium-containing liquid and aluminum oxide; removing impurities from the lithium-containing liquid to obtain an impurity-removed liquid; and reacting the impurity removal liquid with soluble carbonate to obtain lithium carbonate. According to the invention, fluorine in the lithium-containing aluminum electrolyte can be fixed preferentially, and corrosion of fluorine to equipment is reduced. Moreover, the lithium in the lithium-containing aluminum electrolyte can be converted into a precipitation form of lithium-aluminum co-precipitation, so that the difficulty of extracting the lithium is reduced, and the yield of the lithium is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-aluminum electrolyte recovery, and in particular to a method for resource utilization of lithium-aluminum electrolytes. Background Art

[0002] In my country's aluminum electrolysis industry, in order to improve smelting efficiency, low-grade bauxite containing alkali metals such as Li, K, and Ca is usually used as raw material. The content of Li2O in these bauxites can be as high as 0.58%. During the electrolysis process, in order to improve the performance of the electrolyte system, additives such as CaF2, LiF, and KF need to be introduced. With the continuous accumulation and enrichment of the molten electrolyte in the electrolytic cell, a lithium-aluminum electrolyte containing lithium sodium cryolite (LiNa2AlF6) and cathode carbon powder is eventually formed. The lithium-aluminum electrolyte needs to be discharged from the aluminum electrolysis system regularly, but the existing processing technology fails to make full use of the resources in the lithium-aluminum electrolyte.

[0003] At present, the treatment process of lithium-aluminum electrolytes mainly focuses on the leaching and extraction of lithium. However, these processes generally have the problem of low lithium yield in practical applications. Specifically, the existing leaching process often forms a lithium leachate with high fluorine and high aluminum in the process of extracting lithium. In the subsequent step of adjusting the pH value to remove aluminum, the lithium element is often removed along with the aluminum and enters the slag, resulting in a significant reduction in the lithium yield. This not only causes a waste of resources, but also increases the difficulty and cost of subsequent treatment. In addition, the existence of lithium in the slag is diverse, which further aggravates the loss of lithium. For example, the leachate also contains a high sodium content, and some lithium will enter the slag in the form of lithium sodium cryolite (LiNa2AlF6); some lithium will be entrained into the slag by the formed aluminum hydroxide colloid; and some lithium will form lithium aluminum co-precipitation (such as LiY·2Al(OH)3·xH2O, where Y is (SO4) 1 / 2 , Cl, NO3) enter the slag. These complex forms of existence make the extraction of lithium extremely difficult, further aggravating the loss of lithium.

[0004] What is more serious is that the fluorine element in the lithium-aluminum electrolyte will cause serious corrosion to industrial equipment. The longer the fluorine element exists in the system, the more serious the corrosion to the equipment will be, which not only reduces the performance and service life of the equipment, but also increases the operating costs and safety risks of the enterprise. Summary of the invention

[0005] The purpose of this application is to provide a method for resource utilization of lithium-aluminum electrolyte to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for resource utilization of lithium-aluminum electrolyte, comprising:

[0008] The lithium-aluminum electrolyte powder and the fluorine-fixing agent are first calcined to obtain clinker;

[0009] Adding water to the clinker for a first leaching, and obtaining calcium fluoride and a leaching solution through a first solid-liquid separation;

[0010] Adding a soluble aluminum salt and a soluble sodium salt to the leaching solution, heating the solution under alkaline conditions for reaction, and obtaining a lithium aluminum co-precipitate and a post-precipitation liquid through a second solid-liquid separation;

[0011] The lithium aluminum coprecipitate is subjected to a second calcination, water is added to the material after the second calcination for a second leaching, and a lithium-containing liquid and aluminum oxide are obtained by a third solid-liquid separation;

[0012] The lithium-containing liquid is subjected to impurity removal, and a de-impurity liquid and calcium-magnesium slag are obtained by a fourth solid-liquid separation;

[0013] The impurity removal liquid is reacted with a soluble carbonate to obtain lithium carbonate.

[0014] According to an embodiment of the present application, the 150 mesh sieving rate of the lithium-aluminum electrolyte powder is greater than 90%.

[0015] According to an embodiment of the present application, the fluorine-fixing agent includes any one of calcium sulfate, calcium chloride, and calcium nitrate;

[0016] and / or, the ratio of the amount of fluorine in the lithium-aluminum electrolyte powder to the amount of calcium in the fluorine-fixing agent is 1:(1.1-1.5);

[0017] And / or, the temperature of the first calcination is 500° C. to 800° C., and the time of the first calcination is 2 h to 4 h.

[0018] According to an embodiment of the present application, when the first leaching is performed, the solid-liquid ratio of the clinker to water is 1:(3-5) g / mL;

[0019] and / or, the temperature of the first leaching is 80° C. to 100° C.;

[0020] And / or, the first leaching time is 1 hour to 2 hours.

[0021] According to an embodiment of the present application, the soluble aluminum salt includes any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion in the soluble aluminum salt is the same as the anion of the fluorine-fixing agent;

[0022] And / or, the soluble sodium salt includes any one of sodium sulfate, sodium chloride, and sodium nitrate, and the anion in the soluble sodium salt is the same as the anion of the fluorine-fixing agent.

[0023] According to an embodiment of the present application, the amount of the soluble aluminum salt and the soluble sodium salt added satisfies: the molar ratio of aluminum to lithium in the solution after addition is in the range of 2:1 to 6:1, and the molar ratio of sodium to aluminum in the solution after addition is in the range of 3:1 to 8:1;

[0024] And / or, the method further comprises: adding ammonia water to the reaction system to meet the alkaline condition, wherein the pH of the alkaline condition is 8.0 to 10.0;

[0025] And / or, the temperature of the heating reaction is 80° C. to 100° C., and the time of the heating reaction is 2 h to 6 h.

[0026] According to an embodiment of the present application, the temperature of the second calcination is 500° C. to 600° C., and the time of the second calcination is 1 hour to 2 hours.

[0027] According to an embodiment of the present application, when the second leaching is performed, the solid-liquid ratio of the second calcined material to water is 1:(2-3) g / mL;

[0028] and / or, the temperature of the second leaching is 80° C. to 100° C.;

[0029] And / or, the second leaching time is 0.5h to 2h.

[0030] According to an embodiment of the present application, removing impurities from the lithium-containing liquid includes: adding sodium hydroxide to the lithium-containing liquid, adjusting the pH to 12-13, and removing impurities.

[0031] According to an embodiment of the present application, the soluble carbonate includes sodium carbonate.

[0032] Compared with the prior art, the beneficial effects of this application include:

[0033] The method of the present application can preferentially fix the fluorine element in the lithium-aluminum electrolyte by first adding a fluorine-fixing agent, which can effectively reduce the corrosion of fluorine to industrial equipment. Moreover, the method of the present application can convert all the lithium in the lithium-aluminum electrolyte into a precipitation form of lithium-aluminum co-precipitation, which reduces the difficulty of extracting lithium and can effectively improve the yield of lithium. In addition, the method of the present application can efficiently recycle the aluminum, fluorine, and lithium elements in the lithium-aluminum electrolyte, converting them into calcium fluoride, aluminum oxide, and lithium carbonate, a raw material for new energy batteries, used in the smelting industry, to maximize the utilization of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0035] Figure 1 This is a flow chart of the method for resource utilization of lithium-aluminum electrolyte in Example 1. DETAILED DESCRIPTION

[0036] As used herein:

[0037] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0038] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0039] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0040] In these examples, parts and percentages are by mass unless otherwise indicated.

[0041] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0042] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0043] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0044] A method for resource utilization of lithium-aluminum electrolyte, comprising:

[0045] The lithium-aluminum electrolyte powder and the fluorine-fixing agent are first calcined to obtain clinker;

[0046] Adding water to the clinker for a first leaching, and obtaining calcium fluoride and a leaching solution through a first solid-liquid separation;

[0047] Adding a soluble aluminum salt and a soluble sodium salt to the leaching solution, heating the solution under alkaline conditions for reaction, and obtaining a lithium aluminum co-precipitate and a post-precipitation liquid through a second solid-liquid separation;

[0048] The lithium aluminum coprecipitate is subjected to a second calcination, water is added to the material after the second calcination for a second leaching, and a lithium-containing liquid and aluminum oxide are obtained by a third solid-liquid separation;

[0049] The lithium-containing liquid is subjected to impurity removal, and a de-impurity liquid and calcium-magnesium slag are obtained by a fourth solid-liquid separation;

[0050] The impurity removal liquid is reacted with a soluble carbonate to obtain lithium carbonate.

[0051] The method of the present application first fixes the fluorine element in the lithium-aluminum electrolyte, which can shorten the existence time of the fluorine element in the system, reduce the corrosion of the fluorine element to the equipment, and help to extend the performance and service life of the equipment. Moreover, the method of the present application can convert all the lithium elements in the lithium-aluminum electrolyte into the form of lithium-aluminum co-precipitation, which can reduce the difficulty of lithium extraction and effectively improve the yield of lithium. In addition, the method of the present application can achieve comprehensive recovery of fluorine, aluminum, and lithium, and can maximize the utilization of lithium-aluminum electrolyte resources.

[0052] According to an embodiment of the present application, the 150 mesh sieving rate of the lithium-aluminum electrolyte powder is greater than 90%. When the particle size of the lithium-aluminum electrolyte powder is within the above range, the lithium-aluminum electrolyte powder has fine particles and a large specific surface area, which is conducive to sufficient contact and mixing with reactants such as a fluorine-fixing agent, and is conducive to improving the reaction rate and efficiency.

[0053] In some embodiments, the lithium-aluminum-containing electrolyte powder is obtained by ball-milling and crushing the lithium-aluminum-containing electrolyte to obtain the lithium-aluminum-containing electrolyte powder.

[0054] According to an embodiment of the present application, the fluorine-fixing agent includes any one of calcium sulfate, calcium chloride, and calcium nitrate;

[0055] and / or, the ratio of the amount of fluorine in the lithium-aluminum electrolyte powder to the amount of calcium in the fluorine-fixing agent is 1:(1.1-1.5);

[0056] For example, the ratio of the amount of fluorine in the lithium-aluminum electrolyte powder to the amount of calcium in the fluorine-fixing agent can be 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or any value between 1:(1.1 and 1.5).

[0057] And / or, the temperature of the first calcination is 500° C. to 800° C., and the time of the first calcination is 2 h to 4 h.

[0058] For example, the first calcination temperature can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value between 500°C and 800°C, and the first calcination time can be 2h, 3h, 4h or any value between 2h and 4h.

[0059] The reactions that occur during the first calcination process are:

[0060] LiNa2AlF6+CaSO4→Li2SO4+Al2(SO4)3+Na2SO4+CaF2↓

[0061] LiNa2AlF6+CaCl2→LiCl+AlCl3+NaCl+CaF2↓

[0062] LiNa2AlF6+Ca(NO3)2→LiNO3+AlNO3+NaNO3+CaF2↓

[0063] C+O2→CO2↑

[0064] According to an embodiment of the present application, when the first leaching is performed, the solid-liquid ratio of the clinker to water is 1:(3-5) g / mL;

[0065] For example, during the first leaching, the solid-liquid ratio of clinker to water can be 1:3 g / mL, 1:4 g / mL, 1:5 g / mL or any value between 1:(3-5) g / mL.

[0066] and / or, the temperature of the first leaching is 80° C. to 100° C.;

[0067] The temperature of the first leaching may be 80°C, 85°C, 90°C, 95°C, 100°C or any value between 80°C and 100°C.

[0068] And / or, the first leaching time is 1 hour to 2 hours.

[0069] The first leaching time can be 1 hour, 2 hours or any value between 1 hour and 2 hours.

[0070] According to an embodiment of the present application, the soluble aluminum salt includes any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion in the soluble aluminum salt is the same as the anion of the fluorine-fixing agent;

[0071] And / or, the soluble sodium salt includes any one of sodium sulfate, sodium chloride, and sodium nitrate, and the anion in the soluble sodium salt is the same as the anion of the fluorine-fixing agent.

[0072] According to the embodiments of the present application, the added amounts of the soluble aluminum salt and the soluble sodium salt satisfy: the molar ratio of aluminum to lithium in the solution after addition is in the range of 2:1 to 6:1, and the molar ratio of sodium to aluminum in the solution after addition is in the range of 3:1 to 8:1; when the above conditions are met, it is beneficial to convert all the lithium and aluminum elements in the reaction system into a precipitation form of lithium aluminum co-precipitation. The conversion into a precipitation form can reduce the difficulty of subsequent lithium extraction and is beneficial to improving the lithium yield.

[0073] For example, the molar ratio of aluminum to lithium in the solution can be 2:1, 3:1, 4:1, 5:1, 6:1 or any value in the range of 2:1 to 6:1, and the molar ratio of sodium to aluminum in the solution can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or any value between 3:1 and 8:1.

[0074] And / or, the method further comprises: adding ammonia water to the reaction system to meet the alkaline condition, wherein the pH of the alkaline condition is 8.0 to 10.0;

[0075] For example, the pH of the alkaline condition may be 8.0, 9.0, 10.0, or any value between 8.0 and 10.0.

[0076] And / or, the temperature of the heating reaction is 80° C. to 100° C., and the time of the heating reaction is 2 h to 6 h.

[0077] For example, the temperature of the heating reaction can be 80°C, 85°C, 90°C, 95°C, 100°C or any value between 80°C and 100°C, and the time of the heating reaction can be 2h, 3h, 4h, 5h, 6h or any value between 2h and 6h.

[0078] The reaction that occurs during the heating reaction is:

[0079] LiY+2AlY3+6NaOH→LiY·2Al(OH)3·xH2O↓+6NaY

[0080] (Where Y is (SO4) 1 / 2 , Cl or NO3)

[0081] According to an embodiment of the present application, the temperature of the second calcination is 500°C to 600°C, and the time of the second calcination is 1h to 2h. Under the above conditions, the decomposition reaction of the lithium aluminum coprecipitation is facilitated to proceed fully, and the lithium aluminum coprecipitation can be converted into water-soluble LiY and water-insoluble Al2O3, which is conducive to the separation of lithium and aluminum.

[0082] For example, the temperature of the second calcination can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C or any value between 500°C and 600°C, and the time of the second calcination can be 1h, 2h or any value between 1h and 2h.

[0083] The reactions that occur during the second calcination process are:

[0084] LiY·2Al(OH)3·xH2O→LiY+Al2O3+H2O

[0085] (Where Y is (SO4) 1 / 2 , Cl, NO3)

[0086] According to an embodiment of the present application, when the second leaching is performed, the solid-liquid ratio of the second calcined material to water is 1:(2-3) g / mL;

[0087] For example, when the second leaching is performed, the solid-liquid ratio of the material after the second calcination to water can be 1:2 g / mL, 1:2.5 g / mL, 1:3 g / mL or any value between 1:(2-3) g / mL;

[0088] and / or, the temperature of the second leaching is 80° C. to 100° C.;

[0089] The temperature of the second leaching may be 80°C, 85°C, 90°C, 95°C, 100°C or any value between 80°C and 100°C.

[0090] And / or, the second leaching time is 0.5h to 2h.

[0091] For example, the second leaching time may be 0.5 h, 1 h, 1.5 h, 2 h, or any value between 0.5 h and 2 h.

[0092] According to an embodiment of the present application, removing impurities from the lithium-containing liquid includes: adding sodium hydroxide to the lithium-containing liquid, adjusting the pH to 12 to 13, and removing impurities. By removing impurities, impurities such as calcium ions and magnesium ions in the lithium-containing liquid can be removed, which is beneficial to improving the purity of the subsequent lithium carbonate product.

[0093] The reactions that occur during the impurity removal process are:

[0094] Ca 2+ +2OH - →Ca(OH)2

[0095] Mg 2+ +2OH - →Mg(OH)2

[0096] According to an embodiment of the present application, the soluble carbonate includes sodium carbonate.

[0097] The reaction that occurs during the reaction between the impurity removal liquid and the soluble carbonate is:

[0098] 2Li + +CO3 2- →Li2CO3

[0099] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0100] Example 1

[0101] Lithium-aluminum electrolyte composition: Li: 1.68%, F: 20.04%, Al: 35.96%, C: 10.75%, Na: 14.10%.

[0102] Example 1 provides a method for resource utilization of lithium-aluminum electrolyte, referring to Figure 1 ,include:

[0103] S1. Ball milling and crushing the lithium-aluminum electrolyte to obtain a crushed material, wherein the 150-mesh screening rate of the crushed material is 91.17%;

[0104] S2, the crushed material is mixed evenly with calcium sulfate, the amount of calcium sulfate added is according to the amount of F in the lithium-aluminum electrolyte: the amount of Ca in the calcium sulfate = 1:1.4, the roasting temperature is 800°C, the roasting time is 2h, and the fluorine is roasted to obtain clinker;

[0105] S3, the clinker is leached with water, the leaching solid-liquid ratio is 1:5 g / mL, the leaching temperature is 90°C, the leaching time is 1 h, and the first solid-liquid separation is performed to obtain calcium fluoride and a leachate;

[0106] S4, adding aluminum sulfate and sodium sulfate to the leachate to ensure that the molar ratio of Al:Li in the solution is 4:1, and the molar ratio of Na:Al is 5:1, and the mixture is evenly mixed, and then the pH is adjusted to 10.0 with aqueous ammonia. The reaction temperature is 80°C, and the reaction time is 6 hours. The second solid-liquid separation is performed to obtain lithium aluminum co-precipitate and post-precipitation liquid;

[0107] S5, calcining the lithium aluminum coprecipitate at 500° C. for 2 h, then heating and leaching in water, with a solid-liquid ratio of 1:3 g / mL, a leaching temperature of 100° C., and a leaching time of 0.5 h, and performing a third solid-liquid separation to obtain a lithium-containing solution and aluminum oxide;

[0108] S6. Liquid alkali is added to the lithium-containing liquid to adjust the pH to 13 to remove impurities. The fourth solid-liquid separation is performed to obtain an impurity-removing liquid and calcium-magnesium slag. Sodium carbonate is added to the impurity-removing liquid to precipitate lithium carbonate.

[0109] Example 2

[0110] Lithium-aluminum electrolyte composition: Li: 1.76%, F: 22.37%, Al: 32.14%, C: 10.75%, Na: 12.44%.

[0111] Embodiment 2 provides a method for resource utilization of lithium-aluminum electrolyte, comprising:

[0112] S1. Ball milling and crushing the lithium-aluminum electrolyte to obtain a crushed material, the 150-mesh screening rate of which is 90.78%;

[0113] S2, the crushed material is mixed evenly with calcium sulfate, the amount of calcium sulfate added is according to the amount of F in the lithium-aluminum electrolyte: the amount of Ca in the calcium sulfate = 1:1.5, the roasting temperature is 700°C, the roasting time is 3h, and the fluorine is roasted to obtain clinker;

[0114] S3, the clinker is leached with water, the leaching solid-liquid ratio is 1:5 g / mL, the leaching temperature is 80°C, the leaching time is 2 h, and the first solid-liquid separation is performed to obtain calcium fluoride and a leaching solution;

[0115] S4, adding aluminum sulfate and sodium sulfate to the leachate to ensure that the molar ratio of Al:Li in the solution is 5:1, and the molar ratio of Na:Al is 6:1, and the mixture is evenly mixed, and then the pH is adjusted to 8.0 with aqueous ammonia. The reaction temperature is 90°C, and the reaction time is 5 hours. The second solid-liquid separation is performed to obtain lithium aluminum co-precipitate and post-precipitation liquid;

[0116] S5, calcining the lithium aluminum co-precipitate at 600° C. for 2 h, then heating and leaching in water, with a solid-liquid ratio of 1:3 g / mL, a leaching temperature of 80° C., and a leaching time of 1.5 h, and performing a third solid-liquid separation to obtain a lithium-containing solution and aluminum oxide;

[0117] S6. Liquid alkali is added to the lithium-containing liquid to adjust the pH to 13 to remove impurities. The fourth solid-liquid separation is performed to obtain an impurity-removing liquid and calcium-magnesium slag. Sodium carbonate is added to the impurity-removing liquid to precipitate lithium carbonate.

[0118] Example 3

[0119] Lithium-aluminum electrolyte composition: Li: 1.62%, F: 20.20%, Al: 31.66%, C: 11.01%, Na: 11.23%.

[0120] Embodiment 3 provides a method for resource utilization of lithium-aluminum electrolyte, comprising:

[0121] S1. Ball milling and crushing the lithium-aluminum electrolyte to obtain a crushed material, the 150-mesh screening rate of which is 91.80%;

[0122] S2, the crushed material is evenly mixed with calcium sulfate, the amount of calcium sulfate added is based on the amount of F in the lithium-aluminum electrolyte: the amount of Ca in the calcium sulfate = 1:1.2, the roasting temperature is 550 ° C, the roasting time is 4h, and the fluorine is roasted to obtain clinker;

[0123] S3, adding water to the clinker for leaching, the leaching solid-liquid ratio is 1:5 g / mL, the leaching temperature is 100°C, the leaching time is 1h, and the first solid-liquid separation obtains calcium fluoride and a leachate;

[0124] S4, adding aluminum sulfate and sodium sulfate to the leachate to ensure that the molar ratio of Al:Li in the solution is 5:1, and the molar ratio of Na:Al is 7:1, and the mixture is evenly mixed, and then the pH is adjusted to 9.0 with aqueous ammonia. The reaction temperature is 100°C, and the reaction time is 4 hours. The second solid-liquid separation is performed to obtain lithium aluminum co-precipitate and post-precipitation liquid;

[0125] S5, calcining the lithium aluminum co-precipitate at 550° C. for 2 h, then heating and leaching in water, with a solid-liquid ratio of 1:3 g / mL, a leaching temperature of 90° C., and a leaching time of 1.5 h, and performing a third solid-liquid separation to obtain a lithium-containing solution and aluminum oxide;

[0126] S6. Liquid alkali is added to the lithium-containing liquid to adjust the pH to 12 to remove impurities. The fourth solid-liquid separation is performed to obtain an impurity-removing liquid and calcium-magnesium slag. Sodium carbonate is added to the impurity-removing liquid to precipitate lithium carbonate.

[0127] Comparative Example 1

[0128] Comparative Example 1 provides a method for resource utilization of lithium-aluminum electrolytes, which is different from Example 1 in that the 150-mesh screening rate of the crushed material in step S1 of Comparative Example 1 is 80.97%, and other conditions are the same as those of Example 1.

[0129] Comparative Example 2

[0130] Comparative Example 2 provides a method for resource utilization of lithium-aluminum electrolyte, which is different from Example 2 in that: in step S4 of Comparative Example 2, the molar ratio of Al:Li in the solution is 1:1, and the molar ratio of Na:Al is 2:1, and other conditions are the same as those in Example 2.

[0131] Comparative Example 3

[0132] Comparative Example 3 provides a method for resource utilization of lithium-aluminum electrolytes, which differs from Example 3 in that in step S5 of Comparative Example 3, the lithium-aluminum co-precipitate is calcined at 400° C. for 2 h, and other conditions are the same as those of Example 3.

[0133] The yield data of each element in the resource utilization method of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.

[0134] Table 1 Comparison of the yields of each element in the resource utilization methods of Examples 1-3 and Comparative Examples 1-3

[0135]

[0136] Note: Lithium leaching rate in step S3 = lithium mass in leaching solution in step S3 / lithium mass in clinker in step S2 * 100%;

[0137] Lithium leaching rate in step S5 = lithium mass in lithium-containing solution in step S5 / lithium mass in lithium-aluminum co-precipitation in step S4 * 100%;

[0138] Comprehensive lithium yield = lithium mass in lithium carbonate product of step S6 / lithium mass in lithium-aluminum electrolyte of step S1 * 100%;

[0139] Comprehensive yield of fluorine = mass of fluorine in calcium fluoride in step S3 / mass of fluorine in the material after crushing in step S1 * 100%;

[0140] The comprehensive aluminum yield = (the aluminum mass in the alumina of step S5 - the aluminum mass in the soluble aluminum salt of step S4) / the aluminum mass in the material after crushing in step S1.

[0141] From the comparison between Comparative Example 1 and Example 1 in Table 1, it can be seen that the comprehensive yield of lithium, fluorine and aluminum in Comparative Example 1 is significantly reduced compared with Example 1. This is mainly because the 150 mesh screening rate of the material after pulverization in step S1 of Comparative Example 1 is too small, the lithium-aluminum electrolyte and the fluorine-fixing agent fail to fully react in the calcination stage of step S2, lithium and aluminum are not completely converted into soluble lithium salts and aluminum salts, and fluorine is not completely converted into calcium fluoride with the fluorine-fixing agent, resulting in a significantly low comprehensive yield of lithium, fluorine and aluminum.

[0142] It can be seen from Table 1 that compared with Example 2, the lithium content in the liquid after precipitation in step S4 of comparative example 2 is significantly increased. This is mainly because step S4 of comparative example 2 changes the molar ratio of Al to Li and Na to Al, resulting in insufficient Al and Na required for the formation of lithium-aluminum co-precipitation, and lithium cannot be completely embedded in the lithium-aluminum co-precipitate LiY·2Al(OH)3·xH2O, and part of it remains in the liquid after precipitation, resulting in an increase in content.

[0143] It can be seen from Table 1 that compared with Example 3, the comprehensive yield of lithium and aluminum in Comparative Example 3 is significantly reduced, mainly because Comparative Example 3 reduces the calcination temperature of the lithium-aluminum co-precipitation in step S5, so that the decomposition reaction of the lithium-aluminum co-precipitation cannot be fully carried out, and the lithium and aluminum in the lithium-aluminum co-precipitation are not completely converted into LiY and Al2O3, resulting in a significantly low comprehensive yield of lithium and aluminum.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0145] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for resource utilization of lithium-aluminum electrolyte, characterized in that: include: The lithium-aluminum electrolyte powder and the fluorine-fixing agent are first calcined to obtain clinker; Adding water to the clinker for a first leaching, and obtaining calcium fluoride and a leaching solution through a first solid-liquid separation; Adding a soluble aluminum salt and a soluble sodium salt to the leaching solution, heating the solution under alkaline conditions for reaction, and obtaining a lithium aluminum co-precipitate and a post-precipitation liquid through a second solid-liquid separation; The lithium aluminum coprecipitate is subjected to a second calcination, water is added to the material after the second calcination for a second leaching, and a lithium-containing liquid and aluminum oxide are obtained by a third solid-liquid separation; The lithium-containing liquid is subjected to impurity removal, and a de-impurity liquid and calcium-magnesium slag are obtained by a fourth solid-liquid separation; The impurity removal liquid is reacted with a soluble carbonate to obtain lithium carbonate.

2. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The 150 mesh sieving rate of the lithium-aluminum electrolyte powder is greater than 90%.

3. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The fluorine-fixing agent includes any one of calcium sulfate, calcium chloride and calcium nitrate; and / or, the ratio of the amount of fluorine in the lithium-aluminum electrolyte powder to the amount of calcium in the fluorine-fixing agent is 1:(1.1-1.5); And / or, the temperature of the first calcination is 500° C. to 800° C., and the time of the first calcination is 2 h to 4 h.

4. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: When performing the first leaching, the solid-liquid ratio of the clinker to water is 1:(3-5) g / mL; and / or, the temperature of the first leaching is 80° C. to 100° C.; And / or, the first leaching time is 1 hour to 2 hours.

5. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The soluble aluminum salt includes any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion in the soluble aluminum salt is the same as the anion of the fluorine-fixing agent; And / or, the soluble sodium salt includes any one of sodium sulfate, sodium chloride, and sodium nitrate, and the anion in the soluble sodium salt is the same as the anion of the fluorine-fixing agent.

6. The method for resource utilization of lithium-aluminum electrolyte according to claim 5, characterized in that: The amount of the soluble aluminum salt and the soluble sodium salt added satisfies: after addition, the molar ratio of aluminum to lithium in the solution is in the range of 2:1 to 6:1, and the molar ratio of sodium to aluminum in the solution is in the range of 3:1 to 8:1; And / or, the method further comprises: adding ammonia water to the reaction system to meet the alkaline condition, wherein the pH of the alkaline condition is 8.0 to 10.0; And / or, the temperature of the heating reaction is 80° C. to 100° C., and the time of the heating reaction is 2 h to 6 h.

7. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The temperature of the second calcination is 500° C. to 600° C., and the time of the second calcination is 1 hour to 2 hours.

8. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: When performing the second leaching, the solid-liquid ratio of the second calcined material to water is 1:(2-3) g / mL; and / or, the temperature of the second leaching is 80° C. to 100° C.; And / or, the second leaching time is 0.5h to 2h.

9. The method for resource utilization of lithium-aluminum electrolyte according to claim 1, characterized in that: The impurity removal from the lithium-containing liquid includes: adding sodium hydroxide to the lithium-containing liquid, adjusting the pH to 12-13, and removing impurities.

10. The method for resource utilization of lithium-aluminum electrolyte according to any one of claims 1 to 9, characterized in that: The soluble carbonate includes sodium carbonate.